Improving the quality of vocational education through work-based learning in the era of the ASEAN Economic Community - Edwiyan Pradana, Defris Hanindya; Yoto, Yoto; Romadin, Achmad; Permana, Frihandhika; Cendana, Wiputra (Universitas Ngeri Malang, 2023)
In this AEC time, competition can be a benchmark of the significance of progressing the quality of human assets in Indonesia. To respond to current market conditions, it is necessary to have a fast response. The aim is that educational institutions can face the changing global market threat. Education in SMKs must be able to develop and be able to innovate to follow up on opportunities and challenges in the global market. The right solution to this problem is the work-based learning model approach. There are three approaches to learning: first, the practice of fieldwork is a form of development that can be done by vocational education institutions to improve skills not found in the learning process at school and carried out together with the Business World or Industrial World (BW/IW). Second, the industrial class, which is currently widely applied in vocational schools because it is one of the programs considered to be able to bridge the competency gap that exists in schools with BW/IW so that schools can continue to follow the times that can produce skilled workers in the industry. Third, the teaching factory is work-based learning in vocational schools whose output is production/service that alludes to the benchmarks and methods that apply within the industry and are carried out in an atmosphere like that that exists within the industry. Through learning opportunities in practical settings, work-based learning will have an impact on participants and serve as a model for improving the standard of instruction at vocational institutions. Di masa MEA ini persaingan dapat menjadi tolak ukur betapa pentingnya kemajuan kualitas aset manusia di Indonesia. Untuk menyikapi kondisi pasar saat ini, diperlukan respon yang cepat. Tujuannya agar lembaga pendidikan dapat menghadapi ancaman pasar global yang terus berubah. Pendidikan di SMK harus mampu berkembang dan mampu berinovasi untuk menindaklanjuti peluang dan tantangan di pasar global. Solusi yang tepat untuk mengatasi permasalahan tersebut adalah dengan pendekatan model pembelajaran berbasis kerja. Pendekatan pembelajarannya ada tiga, yaitu: pertama, praktek kerja lapangan merupakan suatu bentuk pengembangan yang dapat dilakukan oleh lembaga pendidikan vokasi dalam meningkatkan keterampilan yang tidak terdapat pada proses pembelajaran di sekolah dan dilakukan bersama dengan Dunia Usaha atau Dunia Industri. (BW/IW). Kedua, kelas industri yang saat ini banyak diterapkan di SMK karena merupakan salah satu program yang dianggap mampu menjembatani kesenjangan kompetensi yang ada di sekolah dengan BW/IW, sehingga sekolah dapat terus mengikuti perkembangan zaman. menghasilkan tenaga kerja terampil di industri tersebut. Ketiga, teaching factory, teaching factory merupakan pembelajaran berbasis kerja di SMK yang outputnya berupa produksi/jasa yang mengacu pada tolok ukur dan metode yang berlaku di industri dan dilaksanakan dalam suasana seperti yang ada di industri. Melalui kesempatan pembelajaran dalam suasana praktis, pembelajaran berbasis kerja akan berdampak pada peserta dan berfungsi sebagai model untuk meningkatkan standar pengajaran di lembaga kejuruan.